Structure optimization of positive allosteric modulators of GABAB receptors led to the unexpected discovery of antagonists/potential negative allosteric modulators. Issue 18 (15th September 2020) - Mugnaini, Claudia; Brizzi, Antonella; Mostallino, Rafaela; Castelli, Maria Paola; Corelli, Federico
Graphical abstract: Abstract: Positive allosteric modulators (PAMs) of GABAB receptor represent an interesting alternative to receptor agonists such as baclofen, as they act on the receptor in a more physiological way and thus are devoid of the side effects typically exerted by the agonists. Based on our interest in the identification of new GABAB receptor PAMs, we followed a merging approach to design new chemotypes starting from selected active compounds, such as GS39783, rac -BHFF, and BHF177, and we ended up with the synthesis of four different classes of compounds. The new compounds were tested alone or in the presence of 10 µM GABA using [ 35 S]GTP γ S binding assay to assess their functionality at the receptor. Unexpectedly, a number of them significantly inhibited GABA-stimulated GTPγS binding thus revealing a functional switch with respect to the prototype molecules. Further studies on selected compounds will clarify if they act as negative modulators of the receptor or, instead, as antagonists at the orthosteric binding site.